Teachers’ Lived Experiences and Readiness for Coding and AI Education: A Narrative Case Study from South Kalimantan - Susanti Sufyadi; Sulistyo Rini; Lazaro Kumala Dewi; Adinda Sadilla; Muhammad Afriandy (Yayasan Adra Karima Hubbi, 2026)
Background. The Indonesian government’s policy to introduce coding and artificial intelligence (AI) learning from primary to vocational education has raised critical questions about teacher readiness, particularly in regions outside Java where this dimension is still underexplored. Purpose. This study aims to: (1) map competency standards for teaching coding and AI; (2) analyze teachers competencies readiness; and (3) formulate contextual strategies for teacher capacity building. Method. Using a mixed method, this study involved six teachers from elementary, junior high, and vocational schools in South Kalimantan that have been appointed to implement coding and AI learning. Data were collected through in-depth interviews and questionnaires, then analyzed using the pattern matching analysis model of Vargas and the interactive model of Miles, Huberman, and Saldana. Results. Three key findings emerged: first, competency standards validated by experts. Second, teacher readiness was identified at an average of 74.24%, falling into the